Fuel Consumption Analysis of Injection System and Carburetor System on Honda Beat Fi 2013 - Nyoman Sutarna; I Nengah Ludra Antara; Daud Simon Anakottapary (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
An injection system is a process of burning fuel on an internal combustion engine by using an electronic system to inject fuel with air into the combustion chamber. The carburetor system uses a nozzle to blur the fuel mixture with the combustor air. The purpose of this study was to determine differences in the value of fuel consumption from the injection system with the carburetor system. This research was conducted by the experimental method. The results of the analysis showed that the average value of fuel consumption even with the injection system was 51.53ml, while the mean value of the carburetor system was 90.40 ml, this meant that the injection system was more efficient compared to the carburetor system of 44.89 ml or 47%. Conclusion injection system at any rotation is more economical than the carburetor system. It is recommended to conduct further research by taking real data that is distance and travel time.